2019
DOI: 10.1002/anie.201913129
|View full text |Cite
|
Sign up to set email alerts
|

A Black Phosphorus–Graphite Composite Anode for Li‐/Na‐/K‐Ion Batteries

Abstract: Black phosphorus (BP) is a desirable anode material for alkali metal ion storage owing to its high electronic/ionic conductivity and theoretical capacity. In‐depth understanding of the redox reactions between BP and the alkali metal ions is key to reveal the potential and limitations of BP, and thus to guide the design of BP‐based composites for high‐performance alkali metal ion batteries. Comparative studies of the electrochemical reactions of Li+, Na+, and K+ with BP were performed. Ex situ X‐ray absorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 35 publications
0
72
0
Order By: Relevance
“…Jin et al revealed the distinct charge and discharge behavior of BP in LIBs, SIBs, and PIBs by ex situ XRD. [ 24 ] The results proved that the final product of lithium insertion into BP was Li 3 P, the sodiation counterparts were Na 3 P and NaP, and the potassiation counterparts were K 2 P 3 , KP, and K 3 P (Figure 2i–k). This was due to the unique binding energies of final products when phosphorus formed an alloy with lithium, sodium, and potassium (Figure 2l).…”
Section: Alkaline Metal Ions Storage Mechanismmentioning
confidence: 92%
See 1 more Smart Citation
“…Jin et al revealed the distinct charge and discharge behavior of BP in LIBs, SIBs, and PIBs by ex situ XRD. [ 24 ] The results proved that the final product of lithium insertion into BP was Li 3 P, the sodiation counterparts were Na 3 P and NaP, and the potassiation counterparts were K 2 P 3 , KP, and K 3 P (Figure 2i–k). This was due to the unique binding energies of final products when phosphorus formed an alloy with lithium, sodium, and potassium (Figure 2l).…”
Section: Alkaline Metal Ions Storage Mechanismmentioning
confidence: 92%
“…i-l) Reproduced with permission. [24] Copyright 2019, Wiley-VCH. the second step of alloy reaction to form Na 3 P (Figure 2d).…”
Section: P Anodementioning
confidence: 99%
“…Recently, BP has been intensively studied as an anode material and is considered to be a potential alternative for conventional anode materials. The bulk phosphorus material shows high energy capacity [166][167][168] (2600 mAh g −1 ) with low diffusion energy barrier (0.035 eV and 0.064 eV for Li and Na batteries, respectively) theoretically [165]. During charging, the alkali atoms intercalate into BP layers along zigzag direction accompanied by subsequent expansion along armchair direction because of the shifting from layers.…”
Section: Phase Transition and Solvothermal Reactionmentioning
confidence: 99%
“…Recently, it has been proved by simulation and calculation that BP-based anodes show promising energy storage capabilities in potassium ion batteries (PIBs) [212]; however, only a few phosphorus-based anode materials can reach limited success for K + storage. Jin et al [213] performed a comprehensive study of the electrochemical reactions of Li + , Na + , and K + with BP. The lowest utilization of BP for K + storage than for Na + and Li + has been revealed by ex situ X-ray absorption near-edge spectroscopy combined with theoretical calculation, which contributes to the highest formation energy and the lowest ion diffusion of the final potassiation product K 3 P, as compared with Li 3 P and Na 3 P. As a consequence, restricting the formation of K 3 P by limiting the discharge voltage could provide a gravimetric capacity of 1300 mAh g −1 which retains 600 mAh g −1 even after 50 cycles at 0.25 A g −1 .…”
Section: Sodium-ion Batteries (Sibs) and Beyondmentioning
confidence: 99%
See 1 more Smart Citation